COVID-19 Preparedness and the Anxiety of Thai Citizens - Lateh, Afifi; Pasunon, Prasopchai; Dolah, Kiflan; Kongjam, Panida; Chemae, Saminee; Panomwan, Phanupong; Lateh, Alawee (UI Scholars Hub, 2021)
The outbreak of COVID-19 has brought sickness and fatality to Thai citizens. In addition, it left a tremendous psychological impact on mental health as they experienced panic and anxiety about controlling situations and preserving their physical and mental well-being. This study aimed to analyze the factors influencing COVID-19 preparedness and anxiety based on groups of Thai citizens. Online questionnaires were employed to collect data from 2,768 respondents selected through convenience sampling and snowball sampling on Facebook, having shared questionnaires with 190 other users. Data were collected from March 29 to April 3, 2020. The acquired data were analyzed using percentage and logistic regression analyses. It found that the influencing factors of preparedness included citizens’ sex, residing province, and work or off-house conditions. In contrast, the influencing factors of anxiety included their sex, age, residing province, and income adequacy. The results conveyed that Thai citizens were anxious about the pandemic and had been attempting to cope. In addition, issued policies should respond to the public promptly to prevent unnecessary panic and to maximize public cooperation against future situations put forth by the pandemic.